Manageability of ethnic conflicts - Loone, Eero (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The paper provides a philosophic analysis of issues and hidden assumptions in political theory and in real world situations. Conflict avoidance has been treated as a positive value, although its price could be too high: economic competition involves conflicts. Some conflicts between individuals are unavoidable. Therefore, societies have to develop means and strategies of conflict resolution and conflict management (e.g., warrior-shopkeeper (Nicolson) or imperialist-status quo (Morgenthau) strategies). Conflict avoidance is but one strategy of conflict management. Sometimes ethnicity and race are overlays to other sources of conflict. Agrarian societies are based on unequal access to land-ownership. This may be protected or supported by racial and ethnic differences. Politicians may just express common feelings orexploit these feelings for their own personal and party-political aims, thus creating a second overlay. Estonian land-reform in 1920s and land claims by Blacks in Zimbabwean are examples of these overlays. In some cultures, religion may be a constituent property of a culture and religious conflicts in these cultures are inextricably bound up with conflicts about political power. Religious differences between ethnic groups may strengthen conflicts discursively and behaviourally.
Keywords: nacionalizem; nationalism; democracy; demokracija; večkulturnost; vrednote; konflikti; reševanje konfliktov; upravljanje konfliktov